Effect of Andrographolide on The Expression of TNF-α and Pulmonary Tuberculosis in Rats Granulomas are Infected With Mycobacterium tuberculosis - Y. Slamet Nugroho; Reviono Reviono; Suradi Suradi; Diding Heri Prasetyo (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Background. Andrographolide as an anti-inflammatory inhibit activation of NF-κβ, the production of TNF-α, IL-12, pressing the release inducibele nitic oxide synthase (iNOS), inhibiting the release of COX-2 in human fibroblast cells and also prevents the production of oxygen radicals. TNF- α stimulates the migration of immune cells to get to the site of infection, contribute to the formation of granulomas, and can control the disease progresificity. Methods. The study aims to analyze the effect of andrographolide on the expression of TNF-α and tuberculosis granuloma in mice infected with CFA. Laboratory tests in the laboratory of histology and pathology anatomy medical faculty of UNS. Samples are 30 individuals’ mice, consist of 10 rats as control, 10 rats injected with CFA, and 10 rats injected with CFA+ andrographolide. Histopathology and immunohistochemistry of lung tissue granuloma examinated in the laboratory of pathology anatomy medical faculty of UNS. Results. The study design was purely experimental or (true experiment, with randomized post test only control group design). Andrographolide lowering the average expression of TNF-α compared to the CFA group, based on the description of the variable expression of TNF-α. The results of the analysis of three different variations or the average using Kruskal Wallis test showed that there are differences in the average number 3 granuloma with P=0.003. It means different average number of granulomas in the control group, CFA and CFA+ Andrographolide completely different convincingly. Compared with the average number of granulomas in the control group, the group CFA has a tendency average number of granuloma higher (increased), then the average number of granuloma in group CFA + Andrographolide has an average lower than the group CFA or mean average granuloma amount can be reduced by giving Andrographolide paniculata extract. Conclusion. Andrographolide 14.8% paniculata extract shown to decrease the expression of TNF-α induction of pulmonary tuberculosis in mice the CFA. Andrographolide 14.8% paniculata extract shown to reduce the number of lung granuloma in mice induced tuberculosis CFA. There is a positive correlation between the expression of strong TNF-α by the number of granulomas in the lungs in mice induced tuberculosis CFA. (J Respir Indo 2018; 38(2): 75-82)